Transgender Person and Pre-Exposure Prophylaxis for HIV: A Renal Dilemma - Abu Baker Sheikh; Nismat Javed; Angela Dunn (MDPI AG, 2021)
Sexual health care for transgender people is often inadequate and not addressed. Targeted prevention approaches that respond to the specific needs of transgender individuals are essential to reducing HIV infections. HIV prophylaxis is a proven intervention in the prevention of HIV among high-risk populations. However, creatinine clearance is one major determining factor in prescribing HIV pre-exposure prophylaxis. One of the variables used in the equation to calculate creatinine clearance is gender. Additionally, regarding transgender people, gender-affirming hormonal therapy also alters the clearance by modifying other variables, such as muscle mass. Here, we present the case of a 58-year-old designated female at birth, who transitioned to male 15 months ago, currently using testosterone, and had presented to the clinic requesting HIV pre-exposure prophylaxis, due to his anticipation of new sexual partners soon. He was initially denied HIV pre-exposure prophylaxis, due to lower estimated creatinine clearance when calculated per his natal assigned gender. The transgender population requires effective HIV pre-exposure prophylaxis, dependent on creatinine clearance, that is dictated by many factors, considering the high prevalence rate. Therefore, validation of eGFR equations in the transgender population is of utmost importance to ensure optimal decision-making and provision of health care.